2022
DOI: 10.31234/osf.io/mkvf2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two Sides of the Same Coin: A Mixed Methods Study of Black Mothers’ Experiences with Violence, Stressors, Parenting, and Coping during the COVID-19 Pandemic

Abstract: Due to systemic and structural inequities, the COVID-19 pandemic disproportionately impacts the Black community, along with ongoing anti-Black racism and violence. Violence against women in the home, particularly Black women, was prevalent during shelter in place, along with the additional family responsibilities of Black mothers. Crenshaw’s theory of intersectionality (1991) provides a foundation for examining Black mothers’ experiences during shelter-in-place mandates. This mixed-methods study aimed to quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although most of our participants identified as White, our analysis shows that Black women expressed additional concerns related to racialized violence and systemic racism. These findings are particularly disconcerting when considered alongside racial health disparities in the United States ( Ayoub et al., forthcoming ). Black women experience higher rates of maternal mortality and morbidity (MacDorman et al., 2021 ) yet extant federal policies in the U.S. are consistently ineffectual at combating this health crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Although most of our participants identified as White, our analysis shows that Black women expressed additional concerns related to racialized violence and systemic racism. These findings are particularly disconcerting when considered alongside racial health disparities in the United States ( Ayoub et al., forthcoming ). Black women experience higher rates of maternal mortality and morbidity (MacDorman et al., 2021 ) yet extant federal policies in the U.S. are consistently ineffectual at combating this health crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Confirming these concerns, survey data from more than 900 Black female caregivers in the United States found that Black female caregivers’ financial difficulties during the pandemic were positively related to depressive symptoms, and their increased experiences of racism and concern for children's experiences of racism were positively correlated with loneliness, depression, anxiety, and stress (Ibekwe‐Okafor et al., 2023). Concern for mothers’ mental health, particularly for Black mothers, was also reinforced by a mixed‐method study of approximately 130 Black mothers (Ayoub et al., 2023). This study confirmed that mothers’ perceptions of mistreatment from professionals and awareness of racial disparities in the impact of COVID‐19 was related to greater parental stress, decreased emotional support, greater exposure to physical or sexual violence, and more symptoms of stress, anxiety, and depression.…”
Section: Women's Mental Health During the Covid‐19 Global Pandemicmentioning
confidence: 99%
“…Much of the early empirical research on the COVID‐19 pandemic has been focused on factors related to rates of infection and death. More recently, empirical research has been published related to the disproportionate impacts of COVID‐19 and its inequalities associated with changes in employment and income, race and ethnicity, gender, parenting, and neighborhood characteristics (Ayoub et al., 2022 ; Dawson et al., 2022 ; Fulcher & Dinella, 2022 ; Garland McKinney et al., 2022 ; Geyton & Johnson, 2022 ; Jiwani et al., 2022 ; Rehbein et al., 2022 ; Versey, 2022 ). Additionally, research has more recently been published concentrating on uniquely vulnerable populations such as women, minorities, low socioeconomic households, and the justice‐involved community (Ayoub et al., 2022; Babbar et al., 2022 ; Dawson et al., 2022 ; Fulcher & Dinella, 2022 ; Garland McKinney et al., 2022 ; Geyton & Johnson, 2022 ; Heiman et al., 2022 ; Ibekwe‐Okafor et al., 2022 ; Jiwani et al., 2022 ; Lipp & Johnson, 2022 ; Rehbein et al., 2022 ; Versey, 2022 ).…”
Section: Justice‐involved Mothers: Direct Socioeconomic Impacts Of Co...mentioning
confidence: 99%